2013
DOI: 10.3109/03014460.2012.748093
|View full text |Cite
|
Sign up to set email alerts
|

Structure analysis of the La Guajira-Colombia population: A genetic, demographic and genealogical overview

Abstract: This study found a high level of admixture and gene flow within the Wayúu population despite cultural differences. Thus, although the Wayúu population differs from other population groups, it is not an isolated population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The Wayúu indigenous people speak a language belonging to the Arawak linguistic family, called Wayuunaiki , the Zenú ; on the other hand, despite retaining a lot of their ancestral knowledge, they lost their language soon after the conquest (Arrieta, 2007). Furthermore, the Wayúu people are widely known for the preservation of their culture, and it has been shown that despite there being a high level of admixture and gene flow within their population, they do differentiate genetically from other admixed populations that inhabit the same territory, which suggests the influence of a cultural barrier (Rojas, Alonso, Sarmiento, Eljach, & Usaque, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Wayúu indigenous people speak a language belonging to the Arawak linguistic family, called Wayuunaiki , the Zenú ; on the other hand, despite retaining a lot of their ancestral knowledge, they lost their language soon after the conquest (Arrieta, 2007). Furthermore, the Wayúu people are widely known for the preservation of their culture, and it has been shown that despite there being a high level of admixture and gene flow within their population, they do differentiate genetically from other admixed populations that inhabit the same territory, which suggests the influence of a cultural barrier (Rojas, Alonso, Sarmiento, Eljach, & Usaque, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25% of participants agreed to take part in this genealogical survey, adding a unique dimension to the CARTaGENE project. Indeed, genealogies have proven to be a useful tool to better understand the genetic structure of a population (Abney, 2008;Bherer et al, 2011;Colonna et al, 2009;Gauvin et al, 2014;Larmuseau et al, 2013;Newman et al, 2001;Rojas et al, 2013;Roy-Gagnon et al, 2011;Zaitlen et al, 2013). Considering that the CARTaGENE participants came from four distinct geographical regions of the province of Quebec, a detailed analysis of their genealogical characteristics may bring new insights about the specificities of each regional population.…”
Section: Introductionmentioning
confidence: 99%
“…The area's vegetation consists typically of small trees, rigid stunted perennial bushes, and thorny shrubs. The area is primarily inhabited by the indigenous communities who settled there some 5000 years ago, and have adapted to the harsh surroundings [3]. The peninsula's climate is characterized by the lack of thermal seasons, strong winds, irregular precipitation, and temperatures that can reach highs of between 28 and 33 • C [4].…”
Section: Introductionmentioning
confidence: 99%